The Role And Function Of Phonemes In Phonology For Arabic Communication - Madah Rahmatan; Nurhikmah Sani; Depaty Alvio JH; Diki Ramadhan Alfarisi; Vikky Alziqry JH (International Journal of Education and Teaching Zone, 2023)
Language consists of several language components. Language components are language knowledge, language use, and language changes associated with those components. Language knowledge includes knowledge of phonetics and phonology. Phonetics and phonology are the main understandings in mastering communication using Arabic. In the process of using language, a language is a tool used to convey ideas, thoughts, and desires or desires to others that aim to develop all aspects of life. The research method that the author uses is the Descriptive Qualitative research method. The approach used by the author is the Review Pustaka (Library Research) approach with data collection techniques using the Literature Study method. Phonology comes from the Greek word phono and the word logos. Phono means sound or sound, and the emblem implies science. Phonology is divided into 2 (two), namely phonetics and phonemes. Phonetics is the science of sound that talks explicitly about sound problems without paying attention to the function and meaning of sound. Phonemes are the study of sounds that study parts of the little unity of a language. Vowels in Arabic phonemes are commonly called crazy. Vowel types are the vowel phoneme Fathah, the vowel phoneme Kasrah, and the vowel phoneme Dhommah. A voice or vowel is a language sound that comes from the vibration of a person's throat vocal cords. The difference in the variety of sounds is the long and short verbal aspects.